Searching for the best agarose candidate from genus Gracilaria, Eucheuma, Gelidium and local brands - Ferry Efendi; Retno Handajani; Nursalam Nursalam (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To explore the potential of local agar of genus Gracilaria, Eucheuma, Gelidium and local brands as an alternative for imported agarose for DNA electrophoresis, and to examine their ability related to separation and migration of DNA fragments in DNA electrophoresis. Methods: Their performance at various concentrations were compared via an experimental study with a specific brand of imported commercial agarose used in molecular biology research. The measured variables were separation and migration during electrophoresis of a DNA fragment. Results: The local agar genus Gracilaria gigas, Gelidium, brand “B” and brand “S” could separate DNA fragments at a concentration between 1% and 2%, with an optimum concentration of 2% w/v, as good as a specific brand of imported commercial agarose. Conclusions: Their performance were very close to that of commercial agarose and can still be improved by further agar purification as well as by pH and sulfur control.